First report of Pseudobodo sp, a new pathogen for a potential energy-producing algae: Chlorella vulgaris cultures. - Zhangran Chen; Xueqian Lei; Bangzhou Zhang; Luxi Yang; Huajun Zhang; Jingyan Zhang; Yi Li; Wei Zheng; Yun Tian; Jingwen Liu; Tianling Zheng (PLoS ONE)
Chlorella vulgaris, is a kind of single-celled green algae, which could serve as a potential source of food and energy because of its photosynthetic efficiency. In our study, a pathogenic organism targeting C. vulgaris was discovered. The algae-lytic activity relates to a fraction from lysates of infected C. vulgaris that was blocked upon filtration through a 3 µm filter. 18S rRNA gene sequence analysis revealed that it shared 99.0% homology with the protist Pseudobodo tremulans. Scanning electron microscope analysis showed that Pseudobodo sp. KD51 cells were approximately 4-5 µm long, biflagellate with an anterior collar around the anterior part of the cell in unstressed feeding cells. Besides the initial host, Pseudobodo sp. KD51 could also kill other algae, indicating its relatively wide predatory spectrum. Heat stability, pH and salinity tolerance experiments were conducted to understand their effects on its predatory activities, and the results showed that Pseudobodo sp. KD51 was heat-sensitive, and pH and salinity tolerant.